Application of nordic body map and rapid upper limb assessment for assessing work-related musculoskeletal disorders: A case study in small and medium enterprises - Mohamad, Effendi; Adiyanto, Okka; Faishal, Muhammad; Jaafar, Roshidah; Ma’ruf, Farid; Anggraeni, Anggi (UTHM Publisher, 2022)
Small Medium Enterprise (SMEs) hold a strategic role in economic activities. Since SMEs contribute in enlivening businesses, it is important to assess the SMEs’ performances. One of the most vital aspects in running SMEs is the workers’ productivity which is very risky of declining performance. This study will assess Musculoskeletal Disorder (MSD), one of the workers’ productivity problems. By applying Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA), this study aims to assess work-related MSD in a SME. The NBM questionnaire was used to explore the prevalence of MSD and ergonomic risk factors perceived by the operator. Meanwhile RULA analysis was conducted to know the operator's work position score. The RULA assessment resulted 7 in initial score of employee's position. This score indicated that it immediately required an investigation, further implementation, and changes. From this result, it is necessary to improve a better working position by using a work desk and chair. After the improvement, the RULA score dropped to 3, a good number. The change of operator’s body posture proved that RULA is very important to be further assessed. By doing so, it can be used to offer advice based on ergonomic risk evaluation and expected to increase productivity in SMEs.